99 Bringing the curriculum to life. (12th November 2018) - Okereafor, Akudo; Campbell, Oliver; Ong, Ashley; Jacob, Hannah; Pallawela, Jenny; Jones, Vicky; Davey, Nicola
Abstract : Problem: Lack of knowledge about the new RCPCH curriculum suggested trainees would be unprepared for the new professional requirements. Aim: All paediatric trainees and trainers to be aware and feel confident to use the new curriculum. Measures: Awareness, Confidence Change ideas: Focused on identifying learning in everyday experiences. PDSA#1: Face-to-face presentations. PDSA#2: Night teams highlight an issue at Monday handover using the 'Learning Point from Our Nights' proforma e.g.unusual cases. Team agreement on learning point mapped to new curriculum, proformas shared via WhatsApp. PDSA#3: Short videos created weekly with learning points PDSA#4: Focus on mandatory elements of curriculum. PDSA#5: Online learning platform to catalogue curriculum learning tools. PDSA#6: Sharing with other paediatric departments. Results: Baseline data: 0/27 trainees/trainers felt confident to start using the new RCPCH curriculum.Following a series of interventions there was substantial progress in curriculum knowledge: Those responding 'I've heard of it' fell by 19 . 'I've read about it and know it' rose by 10. 'I feel confident to start using it in August' increased from zero to nine. Conclusions: Driver: a need to understand and know how to use the new RCPCH Progress curriculum ahead of its launch in August. Change ideas mapped to the new curriculum helped paediatric trainees and consultants increase their curriculum knowledge and confidence. Developing a habit of reflection after night shifts facilitates discussions about decision–making and autonomy, identification of real–time problems and promotes team feedback and cohesion . Disseminating completed templates and bite–sized learning videos via WhatsApp and uploading them to a Trello learning platform gave benefit regardless of shift–pattern. Collaborative learning increased our departments' collective knowledge, encouraged evidence–based learning, improved our professional development and will ultimately enrich our patient care.